JURIDICAL ANALYSIS OF THE IMPLEMENTATION OF COACHING FOR NARCOTICS RECIDIVIST INMATES (STUDY IN CLASS II-B BALIGE PRISON) - Kukuh Atian Purba; M. Citra Ramadhan; Andi Hakim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the legal framework governing the guidance of narcotics recidivist inmates, examine the guidance patterns implemented at the Class II-B Balige Detention Center, and identify the obstacles faced by officers in applying such guidance. The research employs an empirical juridical method, combining normative legal analysis with field data obtained from observations and interviews. The findings reveal that the legal basis for inmate guidance is regulated under Law No. 22 of 2022 on Corrections, Government Regulation No. 31 of 1999 on Guidance and Supervision of Correctional Inmates, and Law No. 35 of 2009 on Narcotics. The detention center applies individual and independent guidance patterns tailored to inmates’ needs. However, implementation faces obstacles, including officer negligence and limited supervision, which affect the effectiveness of the correctional system. Strengthening institutional discipline and supervision is essential to prevent recidivism.